Desenvolvimento de software de seleção de bombas centrífugas - Toguti, André Yuji (2025)
The development of efficient pumping systems is fundamental for reducing industrial energy consumption, considering that centrifugal pumps are responsible for more than twenty percent of the energy consumed by electric motors. This work aimed to develop computational software for estimating head loss in piping systems and automated selection of centrifugal pumps, based on the intersection of system and pump characteristic curves. The methodology employed used the Python programming language with scientific libraries such as numpy, matplotlib, pandas, and PyQt6 for graphical interface development. The system was structured into three main modules: hydraulic calculation algorithm based on the Darcy-Weisbach and Colebrook equations for friction factor determination, SQLite database containing characteristic curves of commercial pumps extracted from technical catalogs using Webplotdigitizer software, and selection algorithm that identifies compatible equipment through intersection analysis between system curves and available pumps. Validation was performed through three case studies extracted from academic papers, presenting flow rate differences between -1.94% and 6.17% and head differences between -0.38% and 24.65% compared to reference values. The results demonstrated that the software can provide technically adequate solutions, from small-scale systems to large-capacity installations. The developed tool contributes to automating the centrifugal pump selection process, reducing human errors and standardizing sizing procedures, resulting in energy savings through the selection of more efficient equipment for each specific application.